Unequal Expression: Social Position, APOE Genotype and Risk of Dementia - José M. Aravena; Xi Chen; Becca R. Levy (Global Labor Organization (GLO), 2025)
While most dementia prevention strategies and risk prediction models emphasize biomedical and genetic factors, the influence of genetic risk on dementia also appears shaped by social environments. Following older adults without dementia at baseline for up to 12 years in two large cohort studies-the Health and Retirement Study (HRS) and the English Longitudinal Study of Ageing (ELSA), we examine how APOE alleles interact with social adversity to determine dementia risk. A social adversity index is constructed based on the five domains of social determinants of health outlined in the US Healthy People 2030 framework: education access, economic stability, healthcare quality, neighborhood environment, and social context. Participants are classified as having low (APOE-e2), intermediate (APOE-e3/e3), or high (APOE-e4) genetic risk of dementia. Dementia is ascertained via clinical diagnosis, cognitive testing, or validated caregiver report. Cox proportional hazards models are used in each cohort, and estimates were pooled using random effects adjusting for covariates. Genetic effects are most pronounced among individuals with social advantage. In contrast, those experiencing high social adversity have elevated dementia risk regardless of genotype. Notably, individuals with high genetic risk but social advantage have lower dementia risks than those with low genetic risk but high social adversity. Addressing social adversity may reduce dementia risk across genotypes and enhance equity in dementia prevention strategies.
Keywords: I14; I24; I10; J14; J15; H75; 330; Social Adversity; Social Advantage; Genetic Risk; Genotype; Dementia; United States; United Kingdom